2020
DOI: 10.2147/rmhp.s261489
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Mediating Role of Perceived Stress in Associations Between Self-Compassion and Anxiety and Depression: Further Evidence from Chinese Medical Workers</p>

Abstract: Medical workers report high rates of stress, anxiety and depression, which need urgent attention. Providing evidence for intervention measures in the face of a mental health crisis, the present study validates the relation between self-compassion and anxiety and depression mediated by perceived stress amongst medical workers. The goal is also to replicate a similar mediation model though multigroup analysis. Methods: Medical workers were randomly selected to investigate by paper-and-pencil survey among 1,223 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Compared with direct relationship between self-compassion and depressive symptoms, self-compassion and perceived stress have a much stronger direct relationship in this study. This result highlights the role of self-compassion in defending perceived stress [21,31,39]. The result in this study indicates that self-compassionate people perceive difficulties as a common humanity and tend to treat themselves kindly [30].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Compared with direct relationship between self-compassion and depressive symptoms, self-compassion and perceived stress have a much stronger direct relationship in this study. This result highlights the role of self-compassion in defending perceived stress [21,31,39]. The result in this study indicates that self-compassionate people perceive difficulties as a common humanity and tend to treat themselves kindly [30].…”
Section: Discussionsupporting
confidence: 56%
“…Certain studies have examined the possible mediators between self-compassion and depressive symptoms. For example, the self-compassion-depressive symptoms relationship was mediated by emotion regulation strategies, including rumination, avoidance, and acceptance among adults with recurrent depression (aged 21 -66 years) [17], the ability to tolerate negative emotions among clinically depressed individuals [18], rumination among firstyear psychology undergraduates [19] and breast cancer survivors [20] and perceived stress among medical workers [21].…”
Section: Self-compassionmentioning
confidence: 99%
“…It would be irresponsible to assume that nurses are mentally healthy at all times without attempting to assess the current state of mental health. In the context of the new health care reform, nursing staff are most likely to experience severe perceived stress, anxiety, and depressive symptoms [ 4 ] and are significantly more likely than the general population [ 5 ]. Mental health, job satisfaction, health-related productivity and patient safety among nurses may be negatively impacted by depression [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study among 1233 medical workers from three hospitals in China using a perceived stress questionnaire (PSQ) associated perceived stress with anxiety and depression suggesting it might have a mediating effect. Another study among nursing students in China found a strong association between perceived stress and anxiety [39], [40].…”
Section: Discussionmentioning
confidence: 97%